2016
DOI: 10.1155/2016/3896147
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box-1: A Missing Link between Diabetes and Its Complications

Abstract: High mobility group box-1 (HMGB-1), a damage-associated molecular pattern, can be actively or passively released from various cells under different conditions and plays a pivotal role in the pathogenesis of inflammation and angiogenesis-dependent diseases. More and more evidence suggests that inflammation, in addition to its role in progression of diabetes, also promotes initiation and development of diabetic complications. In this review, we focus on the role of HMGB-1 in diabetes-related complications and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 90 publications
(127 reference statements)
4
47
0
Order By: Relevance
“…Moreover, HMGB1 contributes to cell migration and proliferation, cell differentiation and tissue regeneration [3,20,25], taking part in different pathophysiological processes and diseases, such as sepsis, arthritis, cancer, atherosclerosis, diabetes and cardiovascular diseases [19,[27][28][29][30][31]. HMGB1 is translocated outside the cell in case of cellular damage or cellular death and it was also clearly shown that it can be actively secreted by stimulated immune cells such as monocytes, macrophages, mature dendritic (MD) cells, natural killer (NK) cells and endothelial cells as a result of different stimuli, such as exposure to lipopolysaccharide (LPS), TNF-α, or IL-1β, IFN-γ and tissue injury [3,19,25,[32][33][34]. Furthermore, it has been demonstrated that oxidative stress influences the release of HMGB1 [35].…”
Section: Hmgb1 and Diabetesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, HMGB1 contributes to cell migration and proliferation, cell differentiation and tissue regeneration [3,20,25], taking part in different pathophysiological processes and diseases, such as sepsis, arthritis, cancer, atherosclerosis, diabetes and cardiovascular diseases [19,[27][28][29][30][31]. HMGB1 is translocated outside the cell in case of cellular damage or cellular death and it was also clearly shown that it can be actively secreted by stimulated immune cells such as monocytes, macrophages, mature dendritic (MD) cells, natural killer (NK) cells and endothelial cells as a result of different stimuli, such as exposure to lipopolysaccharide (LPS), TNF-α, or IL-1β, IFN-γ and tissue injury [3,19,25,[32][33][34]. Furthermore, it has been demonstrated that oxidative stress influences the release of HMGB1 [35].…”
Section: Hmgb1 and Diabetesmentioning
confidence: 99%
“…Interestingly, Lu and colleagues showed that translocation from nucleus to cytoplasm, is mediated by JAK/STAT1 pathway [36], and translocation from cytoplasm to extracellular milieu depends on a mechanism mediated by inflammasome activation during pyroptosis, a form of pro-inflammatory programmed cell death [36]. In diabetes condition, hyperglycemia promotes directly or indirectly, through ROS and AGEs production, the release of HMGB1 [32]. It has been demonstrated that HMGB1 is overexpressed in diabetic patients, compared to non-diabetic [37][38][39].…”
Section: Hmgb1 and Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mitogen-activated protein kinase (MAPK) signalling pathways, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 MAPK, are a series of parallel cascades of serine/threonine kinases that are activated by extracellular HMGB1, which also results in the inflammatory response. It is worth mentioning that these inflammatory molecules, in turn, promote additional release of HMGB-1 from cells, resulting in a vicious cycle [8][9][10][11]. GA, also known as Glycyrrhizin, is a triterpenoid triterpene glycoside that is naturally extracted from the roots of licorice plants.…”
Section: Introductionmentioning
confidence: 99%